PENGEMBANGAN MEDIA PAKAPIN DALAM PEMBELAJARAN TEMATIK MUATAN PPKN PADA SISWA KELAS II SD PANGUDI LUHUR ST. ALOYSIUS SEDAYU - Bahan, Sisilia; Nadziroh, Nadziroh; Chairiyah, Chairiyah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
The results are obtained indicate that was: 1) The development of PAKAPIN Media/smart pocket boards has several characteristics in terms of simplicity, emphasis, integration, language, attractiveness, quality, and flexibility. Media PAKAPIN/ Smart pouch board was created using developments from Borg and Gall with potential and problem steps, gathering information, Product design, Product validation, Product improvement, Product Trial, and Product revision. 2) PAKAPIN/Smart Pocket Board media are appropriate to be used as learning media because the results of the study show the value of media experts 77.5 material experts 85.7 ratings from the teacher 86.6 Student responses 89. The average of all assessments obtained is 84.7 which includes in the very good category. and 3). The students gave a very good response to the PAKAPIN Media / Smart Pocket Board.